(untitled) (Asian Journal of Medical and Biological Research, 2016)
The research work was conducted to evaluate the effects of stocking density on growth, survival and production of mirror carp (Cyprinus carpio var. specularis) spawn in nursery pond for a period of 35 days. Three treatments differing in stocking density of hatchling viz., T1:172900 individuals/ha, T2:148200 individuals/ha and T3:123500 individuals/ha were employed each having three replicates. Fries were fed same diet in three different treatments consisting of (28.5%) at the rate of 6-10% of body weight. The Physico-chemical characteristics of pond water were measured weekly. The mean values of some water quality parameters such as temperature (°C) were 30.41 ±1.15 (T1), 30.38±1.08 (T2), 30.45±1.10 (T3); transparency (cm) 40.00±0.90 (T1), 39.74±0.51 (T2), 39.93±0.70 (T3); dissolved oxygen (mg/l) 6.79±0.45 (T1), 6.71±0.38 (T2), 7.02±0.29 (T3); pH 7.55±0.18 (T1), 7.67±0.16 (T2), 7.62±0.20 (T3) and alkalinity (mg/l) 116.20±0.64 (T1), 99.36±0.45 (T2), 96.47±0.93 (T3) from 35 days respectively. Except alkalinity no significant value were found for parameters. Sampling was also done weekly. The mean value of final weight (g) was 0.35±0.004 (T1), 0.42±0.008 (T2), 0.59±0.006 (T3). The survival rate of Cyprinus carpio var. specularis was 54.20% (T1), 62.90% (T2) and 74.56% (T3) respectively. The highest survivability was found in T3. The production (kg/ha) of Cyprinus carpio var. specularis was 76.32±4.96 (T1), 77.60±5.19 (T2), 91.04±6.02 (T3) respectively. Significantly (p< 0.05) highest production was found in T3. Asian J. Med. Biol. Res. September 2016, 2(3): 429-435